Mechanical, durability and thermal properties of foamed concrete reinforced with synthetic twisted bundle macro-fibers - Mydin, Md Azree Othuman; Mohd Nawi, Mohd Nasrun; Omar, Roshartini; Dulaimi, Anmar; Mohammed Najm, Hadee; Mahmood, Shaker; Sabri, Mohanad Muayad (Frontiers, 2023)
The use of foamed concrete (FC) in the construction sector has been rapidly growing over the past few years as a result of the several advantages it possesses in comparison to traditional high-strength concrete. FC, on the other hand, suffers from a number of deficiencies, such as brittleness, limited ductility, high porosity, excessive drying shrinkage, little resistance to cracking and deformation. To improve the tensile strength and fracture resistance of FC, engineers usually opt for steel fibre or polymer fibre as the reinforcement material of choice. Hence this research aims to investigate the potential utilization of synthetic twisted bundle macro-fibers (SF) in FC to enhance its durability, mechanical and thermal properties. The SF were included in the FC in varied amounts of weight fractions, including 0%, 1%, 2%, 3%, 4%, and 5% respectively. FC was produced at three low densities, precisely 1,000, 1,300, and 1,600 kg/m3, which were all prepared. Compression, fLexural, splitting tensile, fLow table, porosity, water absorption and thermal conductivity tests were conducted to establish the thermal, mechanical and durability properties of SF-reinforced FC. The findings imply that the integration of SF into FC results in a significant enhancement of the material’s strength and thermal conductivity properties while simultaneously lowering the material’s capacity for water absorption and porosity. For the purpose of improving the material’s mechanical, durability and thermal properties, the weight percentage of SF that was ideal ranged from 3% to 4%. The incorporation of SF into FC resulted in a rise in the material’s ductility, and the specimens maintained their integrity from the loading stage to failure. The SF is able to lessen the cracks that were already present in the FC and prevent the formation of additional cracks in the FC.